2019
DOI: 10.1111/jace.16386
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced spontaneous polarization in double perovskite Bi2FeCrO6 films

Abstract: We report the pulsed‐laser deposition of epitaxial double‐perovskite Bi2FeCrO6 (BFCO) films on the (001)‐, (110), and (111)‐oriented single‐crystal SrTiO3 substrates. All of the BFCO films with various orientations show the 1-0.166667emtrue/21-0.166667emtrue/21-0.166667emtrue/2 and 3-0.166667emtrue/23-0.166667emtrue/23-0.166667emtrue/2 superlattice‐diffraction peaks. The intensity ratios between the 1-0.166667emtrue/21-0.166667emtrue/21-0.166667emtrue/2‐superlattice and the main 111‐diffraction peak can be tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The optical transmittance of BM-SCO is weak in the visible light region and significantly enhanced in the infrared region, while PV-SCO is nearly opaque in both the visible light and infrared regions. Figure b indicates the relationship between the photon energy ( hv ) and (α hv ) 2 plot obtained from the optical absorption spectra (Figure S4), where α is the optical absorption coefficient, which can estimate the direct bandgap of two phases . Accordingly, the direct bandgap of BM-SCO is approximately 2 eV, which causes the difference in optical transmittance from the visible light to the infrared region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical transmittance of BM-SCO is weak in the visible light region and significantly enhanced in the infrared region, while PV-SCO is nearly opaque in both the visible light and infrared regions. Figure b indicates the relationship between the photon energy ( hv ) and (α hv ) 2 plot obtained from the optical absorption spectra (Figure S4), where α is the optical absorption coefficient, which can estimate the direct bandgap of two phases . Accordingly, the direct bandgap of BM-SCO is approximately 2 eV, which causes the difference in optical transmittance from the visible light to the infrared region.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4b indicates the relationship between the photon energy (hv) and (αhv) 2 plot obtained from the optical absorption spectra (Figure S4), where α is the optical absorption coefficient, which can estimate the direct bandgap of two phases. 35 Accordingly, the direct bandgap of BM-SCO is approximately 2 eV, which causes the difference in optical transmittance from the visible light to the infrared region. The difference in the optical performance of the two phases creates an application in smart windows.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These films were reported to show enhanced spontaneous polarization. [ 66 ] Figure 9 clearly illustrates the interdependency between crystal orientation and the ferroelectric properties.…”
Section: Part Ii: Other Laser Methods For Pscsmentioning
confidence: 99%
“…Epitaxially grown double perovskite Bi 2 FeCrO 6 films on the (001)-, (110)-, and (111)-oriented single-crystal SrTiO 3 substrates were prepared by PLD as reported by Meng et al These films were reported to show enhanced spontaneous polarization. [66] Figure 7. a) Device architecture of laminated perovskite solar cell/module.…”
Section: Inorganic Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation